Pengadaan Tong Sampah Organik Dan Anorganik Di Desa Nanggerang Kecamatan Cililin Kabupaten Bandung Barat - Sahra Fajrin Dytiar (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Nanggerang Village is located in West Bandung Regency, Cililin District, West Java Province. The main livelihood of the people of Nanggerang Village is mostly farming and animal husbandry. However, awareness and concern for waste management among Nanggerang Village residents is still lacking. Local people believe that burning rubbish is the quickest solution to solving the rubbish problem in their village. The public is starting to realize the importance of waste management as a result of these efforts. Because not only does it help protect the environment, but it can also boost the local economy by teaching people how to make valuable, salable items out of waste. Since they can create something out of trash with their own hands, waste control strategies for kids make them happy. The hope is that in the future their creativity in dealing with waste problems will be honed even more and cadres who care about the environment will emerge in their village. Apart from that, by providing rubbish bins in Nanggerang Village, the community can carry out practical waste management activities by classifying organic and non-organic waste.